The competitive edge of bilingualism on the job market - Abdullah, Ain Nadzimah; Talif, Rosli (Journal of Modern Languages, 2017)
The purpose of this study is to evaluate perceptions towards BM-English knowing bilingualism and its profitability for executive-level employees in the job market. Knowing both BM and English in Malaysia promote the ability to communicate and interact with a wide range of people and allows one to gain access to knowledge sources thus bringing social, cognitive, and economic advantages to a person.